Lessons Learned from Three Decades of Experience with Cap-and-Trade - Richard Schmalensee; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2015)
This essay provides an overview of the major emissions trading programs of the past thirty years on which significant documentation exists, and draws a number of important lessons for future applications of this environmental policy instrument. References to a larger number of other emissions trading programs that have been implemented or proposed are included.
Keywords: Q54; Q58; Q40; Q48; 330; Market-based instruments; Cap-and-trade; Leaded Gasoline Phasedown; Clean Air Act Amendments of 1990; Sulfur Dioxide; Acid Rain; Carbon Dioxide; Global Climate Change; European Union Emissions Trading System